The role of the transport sector in climate change mitigation: An interdisciplinary approach to mobility innovation - Nichi, Jaqueline (Seven Editora, 2023)
This article addresses the relevance of the transport sector in climate change mitigation and adaptation strategies, with a special focus on the Brazilian scenario, in which it represents 65% of energy consumption. Road transport, responsible for 13% of total carbon dioxide equivalent (CO2e) emissions in the sector, stands out as the main emitter. In addition to emphasizing the importance of urban planning, the potential for reducing emissions through an interdisciplinary approach that combines multi-level governance and low-carbon technologies are explored. Solutions such as more compact cities, the use of clean energy, and the integration of different modes, with an emphasis on public transport, are discussed as smart and sustainable strategies. This article also conducts a theoretical review of the current literature on smart mobility and its climate impacts, analyzing opportunities and challenges from the perspective of multilevel socio-technical transition. To illustrate the application of these ideas, we present a case study focused on the mobility system of the city of São Paulo, with the aim of understanding the barriers and opportunities towards a transport permeated by innovative and carbon-neutral technologies. DOI:https://doi.org/10.56238/interdiinovationscrese-072